2007
DOI: 10.1016/j.geoforum.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Good governance in the Pacific? Ambivalence and possibility

Abstract: In September 2005, the Pacific Islands Forum issued a finalized Pacific Plan. The overarching goal of the Plan is to ''Enhance and stimulate economic growth, sustainable development, good governance and security for Pacific countries through regionalism.'' In this paper we focus on the salient role of (good) governance in the Plan. Governance has become a keyword, albeit a deeply ambivalent one, in development and foreign policy realms and the Pacific is now a particularly intense site of activities understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Just as we saw in the Pacific Plan example (Roberts/Wright/O'Neill 2007), it is often stated in critical corruption literature that the current dominating anti-corruption discourse is too focused on technical solutions and the public-private distinction, resulting in too much attention to the public sector as the major cause of corruption. In short, the 'anti-corruption crusade needs to be shorn of its anti-state bias' (Brown/Cloke 2004: 291).…”
Section: Power and The Consequences Of Anti-corruption Discoursesmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as we saw in the Pacific Plan example (Roberts/Wright/O'Neill 2007), it is often stated in critical corruption literature that the current dominating anti-corruption discourse is too focused on technical solutions and the public-private distinction, resulting in too much attention to the public sector as the major cause of corruption. In short, the 'anti-corruption crusade needs to be shorn of its anti-state bias' (Brown/Cloke 2004: 291).…”
Section: Power and The Consequences Of Anti-corruption Discoursesmentioning
confidence: 99%
“…Building partly on the work of Foucault, some have shown how discourses on corruption with their inherent worldviews give some an advantage over others. For example, Roberts et al (2007) have shown how the discourse on governance in the so-called Pacific Plan resulted in a technocratic direction such that a particularly narrow conceptualization of governance dominates. 'In a direct reading of the Pacific Plan and the interventions it empowers there is ample evidence that governance (good and bad) is used in a disciplining way' (Roberts/Wright/O'Neill 2007: 981).…”
Section: Power and The Consequences Of Anti-corruption Discoursesmentioning
confidence: 99%
“…Earlier, this term is widely introduced by institutions donors in the form of technical assistance and international cooperation in developing countries. World Bank publication in 1992 on governance and development, has introduced the concept of good governance (De Graaf et al, 2011;Roberts et al, 2007;Effendi, 2005). It can be caused by the power of the World Bank in 'pressing' the lending countries to accept a variety of programs offered.…”
Section: Approach Principles and Components Of Good Governance: Accomentioning
confidence: 99%
“…However, the role of governments in governance and their accountability towards protection of society and the environment is a fundamentally accepted norm today. In particular, the concern attached to bad governance is most often directed at governments (Roberts, Wright, & O'Neill, 2007).…”
Section: Governance (Risk): a Cause And A Remedy For Development Disamentioning
confidence: 99%
“…Good governance is represented by the 'presence' of these elements in a society (Roberts et al, 2007). Access to information on disaster risk, particularly for the most vulnerable, is considered as the first step in effective DRR (UNISDR, 2011).…”
Section: Governance (Risk): a Cause And A Remedy For Development Disamentioning
confidence: 99%